A comparative study of secure hash algorithms - Gupta S.; Yadav S.K.; Singh A.P.; Maurya K.C. (My University, 2025)
Important responsibility of every organization is to provide an adequate security and confidentiality to its electronic data system. Data should be protected during transmission or while in storage it is necessary to maintain the integrity and confidentiality of the information represented by the original data. Message digests are the condensed representation of a message after processing that message through some mathematical algorithm which is iterative in nature and one way. Integrity of message is ensured by these algorithms: any change to the message, with a very high probability, results in a different message digest. This paper explains the implementation of all available secure hash algorithms (SHA) and their performance evaluation. Performance evaluation has been done in terms of security. Randomness of all the hash algorithms have been evaluated with K-S, Chi Square and Autocorrelation tests. It is observed that all available SHAs are very useful in their area of applications because they produce totally random output even if their input is highly correlated. Hence it is found that a very high level of security attained using hash algorithms. It has been observed that SHA-512 provides a very high level of security because it has 512 bits inside which are randomly distributed but it is a bit lengthy and time taking. © Springer International Publishing Switzerland 2016.